PrEP15-19 Choices: an implementation study protocol of HIV prevention with oral and long-acting injectable cabotegravir PrEP in real-world settings among sexual and gender minority adolescents in Brazil - Inês Dourado; Eliana Miura Zucchi; Laio Magno; Alexandre D Grangeiro; Márcia Thereza Couto; Mateus Westin; Eduardo Oliveira; Maria Mercedes Escuder; Dirceu Greco; Thais Regis Aranha Rossi; Fabiane Soares; Lorenza Dezanet; et al. (BMJ Open)
Introduction Long-acting injectable (LAI) cabotegravir is a promising new method for preventing HIV. Safe and effective long-acting agents for pre-exposure prophylaxis (PrEP) for HIV infection are needed to increase preventive options among sexual and gender minority adolescents.Methods and analysis This is a multisite, prospective implementation study of three PrEP modalities (LAI-PrEP, event-driven (ED) and daily oral), using a mixed-method design with quantitative and qualitative approaches. The study will include a sample of 550 HIV-negative adolescent men who have sex with men, non-binary individuals assigned male at birth, transgender men and women, aged 15–19 years, in three Brazilian capital cities. Participants will be allocated into two arms, according to their choice of PrEP modalities, and followed up to 36 months. Switching between oral and LAI-PrEP will be allowed, according to the participants’ needs and preferences. The qualitative studies will focus on investigating the processes involved in linkage and retention in care, switching between PrEP modalities and strategies of the implementation process of LAI-PrEP in the current PrEP programming and acceptability from health providers, policymakers and stakeholders’ perspectives.Ethics and dissemination The adolescent’s autonomy for consenting to their participation and understanding of PrEP will be assessed by the project team before any care is given and will be recorded in their medical record. Adolescents aged 15–17 years will sign an informed assent form, waiving the need for the approval of a legal guardian, except in cases where the adolescent is found not to have the necessary autonomy. The study was approved by the WHO Ethics Review Committee and by the local IRBs from the universities coordinating the study, the University of São Paulo, the Federal University of Bahia and the Federal University of Minas Gerais. This project is part of an effort to expedite the inclusion of new modalities in the Brazilian PrEP Programme, based on the development of studies to evaluate the implementation of LAI-PrEP and ED-PrEP as a choice. The results will be published in peer-reviewed journals and presented to the study participants and communities.Trial registration number https://ensaiosclinicos.gov.br/rg/RBR-104736f4. The trial registration number: RBR-104736f4